Organizational Resources Capability of the Government Internal Supervisory Apparatus (APIP) in Conducting Financial Audits in Takalar Regency - Nugraha, Hendrawan Agustian; Ibrahim, Muh Akmal; Badu, Badu; Sukri, Sukri (AIBPM Publisher, 2024)
This qualitative case study examines the organizational resource capability of the Government Internal Supervisory Apparatus (APIP) in conducting financial audits in Takalar Regency, Indonesia.The research focuses on analyzing APIP's resources, including routine combinations, specific objectives, non-tradability, and organizational strategy. Data was collected through observations, in-depth interviews, and documentation. The findings reveal that APIP Takalar Regency has a structured auditor competency level, systematic work mechanisms, quality-focused auditor recruitment, and continuous competency development. However, challenges exist in auditor shortages and maintaining independence with local auditors. Achieving audit objectives requires support and commitment from supervisors and Regional Apparatus Organizations (OPD). Efforts to maintain auditor integrity, independence and objectivity include higher allowance policies and a code of ethics. However, APIP's position under the Regent poses dilemmas in reporting potentially unfavorable audit results. APIP's organizational strategy is based on HR development, key performance indicators, HR improvement budgets, and auditor training programs. Increasing APIP's capability level is a key objective